Air Quality Analysis of Ulaanbaatar : Improving Air Quality to Reduce Health Impacts - World Bank (World Bank, Washington, DC, 2017)
Air pollution has major health impacts on people living in Ulaanbaatar. The excessively high particulate matter concentrations, especially in the winter and in the ger areas, increase the incidence of heart and lung diseases, and lead to premature deaths. Improving air quality management in Ulaanbaatar and reducing pollution concentrations would prevent illnesses, save lives and avoid enormous health costs. The implementation of the Air Monitoring and Health Impact Baseline (AMHIB) study has brought together Mongolian and international air quality experts as well as public health experts and economists who have taken an synergetic approach of linking public health, air quality and economic issues. This report builds upon the discussion paper air pollution in Ulaanbaatar: initial assessment of current situation and effects of abatement measures that was published in December 2009, and reflects the final results and recommendations from the AMHIB project.